The assessment of the influence of styrene-butadiene-styrene copolymer on the selected rheological properties characterising durability of modified bitumens used in road pavements - Mielczarek, M; Dziadosz, S; Słowik, M; Bilski, M (Bulletin of the Polish Academy of Sciences. Technical sciences, 2020)
The subject matter of the research pertains to the improvement of rheological properties of petroleum bitumens by their modification with SBS (styrene-butadiene-styrene) copolymer. The authors have determined selected rheological properties characterising the durability of modified bitumens used in road pavements. The bitumens were modified in laboratory conditions with modified bitumen concentrate of a known SBS copolymer content of 9%. The result was a binder containing the known percentage of the SBS copolymer of 3%, 4.5% and 6%. Rheological properties of the tested bitumens were determined by the use of a DSR dynamic shear rheometer (in a wide temperature range from 40°C to 100°C) and a ductilometer at 5°C. DSR was used for performing MSCR test to determine the resistance of the asphalt mixture with the SBS-modified binder to permanent deformations in the high temperature range (from 40°C to 82°C). The comparison of the values of the dynamic shear modulus |G*| of all the bitumens tested shows that with a growing content of the SBS copolymer in the tested binder the value of |G*| increases, which may indicate greater resistance to permanent deformation of the asphalt pavement. The MSCR test has shown that the increased use of the SBS copolymer addition in the bitumen translates to decreasing values of the non-recoverable creep compliance Jnr. The SBS copolymer accelerates stress relaxation in the bitumen sample, thus increasing pavement resistance to low-temperature cracks. Furthermore, modification reduces the negative impact of ageing on the properties of the binder, manifested by its stiffening and slowdown of relaxation.